English for customer care - Richey, Rosemary (Oxford University Press, 2007)
"English for customer care" has been developed for people working in customer service who need a good level of English. You might be working in the sales or customers in a bank or hotel. Or perhaps you speak to customers on the telephone from a helpdesk or a call centre. In all of these situations you need language skills and specific techniques in order to be able to communicate successfully. This book not only offers expressions and vocabulary, it also addresses strategies related to the effective use of English in a business context.